Perioperative Analgesia in Cats Undergoing Elective Ovariohysterectomy - Preemptive use of Carprofen or Grapiprant - Gasparotto, Jean; Gonçalves Teixeira, Luciana; Vanessa Vaccarin, Charline; Ivanir Schimites, Paula; Tonietto Mangini, Luiza; Mariani Griesang, Julia; Vargas, Daniel; Bortolotto Degregori, Emanuelle; Vasconcelos Soares, André (Acta Scientiae Veterinariae, 2023)
Background: The nonsteroidal anti-inflammatory drugs (NSAIDs) exert their analgesic effect through peripheral inhibition of prostaglandin synthesis and a variety of other peripheral and central mechanisms. However, NSAIDs are associated with some adverse effects, mainly related to the gastrointestinal, renal, and hepatic systems, highlighting the need for research to develop safer drugs. Therefore, the aim of this study was to evaluate the efficacy of preoperative oral administration of carprofen or grapiprant in female cats submitted to elective ovariohysterectomy on the quality of perioperative analgesia and the need for hypnotic and analgesic drugs. Materials, Methods & Results: Thirty-three adult female cats were selected, without defined breed and healthy based on physical examination, routine laboratory analyses (complete blood count, total protein, Heinz body investigation and serum quantification of alanine transaminase [ALT], aspartate transaminase [AST], gamma glutamyl transpeptidase [GGT], alkaline phosphatase [ALP], urea, frutosamine, and glucose) and negative tests for feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV). After 3 days of adaptation, they were submitted to ovariohysterectomy by celiotomy and randomly allocated into 2 groups according to the preoperative drug used: GCAR [carprofen - 4 mg/kg, VO, 2 h before surgery; n = 11] and GGRA (grapiprant - 2 mg/kg IV, 2 h before surgery; n = 21]. The cats were pre-medicated with acepromazine 0.05 mg/kg IV and later submitted to general anesthesia with propofol intravenously. Anesthesia was maintained with isoflurane in 100% oxygen. After anesthetic induction, a continuous infusion of remifentanil at a rate of 10 μg/kg/h was initiated. During the transanesthetic period, the parameters of heart rate; respiratory rate; systolic, mean, and diastolic arterial pressure using the oscillometric method; electrocardiogram; rectal temperature; partial pressure of CO2 at the end of expiration: and partial saturation of O2 in hemoglobin were continuously monitored. The evaluation of nociception was based on the changes in the aforementioned physiological parameters. The rate of remifentanil used did not change over time with the use of carprofen. However, animals that received grapiprant required a lower remifentanil dose at 20, 25, and 30 min during the procedure. The female cats that received carprofen showed an increase in mean heart rate at 30 min compared to that at 20 and 25 min. In the Grapiprant group, the heart rate at 35 min was higher only than that observed at 25 min. Discussion: The remifentanil rate did not differ between the groups, even between the times for GCAR. However, the remifentanil rate was lower from 20 min of the procedure for GGRA. This decrease may be related to a decrease in the need for anesthetics and analgesics by decreasing temperature, which causes decreases in metabolism and surgical stimulation. The increase in systolic, mean, diastolic, and heart rate arterial pressure parameters observed in both treatments after 15 min of anesthesia is related to the nociceptive stimulus resulting from traction and ligation of the ovarian pedicles and maneuvers for exteriorization of the uterus. These are considered the moments of greater surgical stimulus during ovariohysterectomy, evidenced by the greater release of cortisol and increase in physiological parameters. The results of this study show that the administration of carprofen or grapiprant was clinically similar when used preemptively for perioperative analgesia in cats submitted to elective ovariohysterectomy. Keywords: cats, NSAIDs, grapiprant, perioperative analgesia, nociception. Título: <span dir="ltr" style="left: calc(var(--scale-factor)*79.16px); top: calc(var(--scale-factor)*110.44px); font-size: calc(var(--scale-factor)*13.00px); font-family: sans-serif; transform: scaleX(1.00952);" role="presentation">Analgesia perioperatória de gatas submetidas a ovariohisterectomia eletiva <span dir="ltr" style="left: calc(var(--scale-factor)*166.64px); top: calc(var(--scale-factor)*126.04px); font-size: calc(var(--scale-factor)*13.00px); font-family: sans-serif; transform: scaleX(1.01445);" role="presentation">- uso preemptivo de carprofeno ou grapiprant Descritores: gatos, AINES, grapiprant, analgesia perioperatória, nocicepção.